ANALISIS MISKONSEPSI SISWA PADA MATERI PECAHAN DALAM BENTUK ALJABAR DITINJAU DARI GAYA KOGNITIF SISWA KELAS VIII DI SMP NEGERI 2 ADIMULYO KABUPATEN KEBUMEN TAHUN AJARAN 2013/2014 - Savitri, Maria Endah; Mardiyana, Mardiyana; Subanti, Sri (Jurnal Pembelajaran Matematika, 2016)
Abstract: The purposes of this research were to: (1) identify the occurrence of misconceptions in the eighth grade junior high school students in the material form of algebraic fractions, for students which are classified to cognitive style field independence and field dependence, and (2) describe the occurrence of misconceptions eighth grade junior high school students in the material form of algebraic fractions, for students which are classified to cognitive style field independence and field dependence. This research used a descriptive qualitative Â method with a case study. Subjects of this research are eighth grade students of SMP Negeri 2 Adimulyo academic year 2013/2014. The sample of the research was taken by using the snowball sampling technique. The identification of the existence of misconceptions was done by using misconception diagnostic test. While the identification of the students cognitive styles was conducted by using student cognitive style questionnaire instrument. Data validity used the source of triangulation method. Analysis of data use the model of Miles and Huberman. The results of this research indicate that: (1) misconceptions that occur in the FD students more likely to misconceptions on the concept of understanding the elements of the algebra and the terms of a fraction is called fractional form algebra, the concept of canceling, the concept of operating powers, and understand the properties the concept of distributive, (2) the highest misconceptions experienced by the FI students in understanding the concept of distributive properties, as well as understanding the elements of the algebra the condition is referred to as a fraction in the form of algebraic fractions, (3) causes of the misconceptions students FD is dominated by reasoning is not complete and students who lack of ability to process and memorize course, (4) factors causing of misconceptions students FI dominated by reasoning is not complete.Keywords: Misconceptions, algebraic fractions, cognitive style.